2015
DOI: 10.5336/anesthe.2015-45739
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Segmental Epidural Levobupivacaine Administration and Wound Infiltration Following Posterior Fusion Surgery: A Case Serie

Abstract: A AB BS S T TR RA AC CT T O Ob bj je ec ct ti iv ve e: : The current study aimed to provide intraoperative smooth wake-up test and postoperative effective analgesia by segmental epidural analgesia and wound infiltration in patients undergoing posterior fusion surgery. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : Fifteen ASA I-II adolescent patients aged 11-16 undergoing posterior fusion and instrumentation were included to the study. After general anesthesia with standard intravenous anesthesia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…CWI with local anesthetics via catheters placed in the surgical wound before closure prevents nociceptive impulses, relieves postoperative pain, 62 and can have significant opioid sparing effect. 60 A recent retrospective chart review of 81 patients found that in addition to IV PCA and oral opioids, CWI bupivacaine provided via elastomeric pumps was associated with clinically and statistically significant improvements in postoperative course, and that the addition of multimodal pain management with gabapentin and methocarbamol was associated with trends toward JPOSNA Volume 3, Number 3, August 2021…”
Section: Continuous Wound Infiltration (Cwi)mentioning
confidence: 99%
See 1 more Smart Citation
“…CWI with local anesthetics via catheters placed in the surgical wound before closure prevents nociceptive impulses, relieves postoperative pain, 62 and can have significant opioid sparing effect. 60 A recent retrospective chart review of 81 patients found that in addition to IV PCA and oral opioids, CWI bupivacaine provided via elastomeric pumps was associated with clinically and statistically significant improvements in postoperative course, and that the addition of multimodal pain management with gabapentin and methocarbamol was associated with trends toward JPOSNA Volume 3, Number 3, August 2021…”
Section: Continuous Wound Infiltration (Cwi)mentioning
confidence: 99%
“…63 An earlier randomized, prospective, double blinded study with 30 participants investigating the use of CWI and epidural anesthesia in addition to IV PCA concluded that this combination was an "effective and simple method" for postoperative analgesia with significant reductions in postoperative morphine consumption and VAS pain scores versus a control group receiving IV PCA alone. 62 A retrospective chart review of 107 patients in 2011 found that compared to narcotic and non-narcotic PCA, postoperative wound irrigation with 0.1-0.2% ropivacaine in combination with NSAIDs was more effective in that it provided for earlier feeding and reduced incidence of vomiting. 23…”
Section: Continuous Wound Infiltration (Cwi)mentioning
confidence: 99%